Calculations of the mechanical, optoelectronic, and magnetic properties of FrGeX3 (X = Cl, Br, I) under hydrostatic pressures based on first-principles theories - M. D. Ratul Hasan; Imtiaz Ahamed Apon; Istiak Ahmed Ovi; Mohammad Salman Haque (AIP Advances, 2024)
Using first-principles calculations based on density functional theory, this work investigated the mechanical, magnetic, elastic, electrical, and optical characteristics of the halide-based perovskite FrGeX3 (X = Cl, Br, I) at different hydrostatic pressures ranging from 0 to 9 GPa. It was determined that the compound FrGeX3 (X = Cl, Br, I) is stable and ductile in nature by calculating its thermodynamic and mechanical stability using the parameters of its formation enthalpy and elastic constant. When no hydrostatic pressure is applied, the band computations reveal that FrGeCl3, FrGeBr3, and FrGeI3 all remain in the semiconductor region with bandgaps of 1.14, 0.8, and 0.645 eV, respectively. The study examined how increasing induced pressure affects the bandgap and density of states of the structure for all three halides. The bandgap of FrGeCl3, FrGeBr3, and FrGeI3 fell to 0 eV at 9, 6, and 5 GPa, respectively. In addition, the optical absorption, reflectivity, refractive index, and imaginary and real components of dielectric functions were all studied in detail for cubic perovskites FrGeX3 (X = Cl, Br, I) under varying hydrostatic pressures, from 0 to 9 GPa. Due to increased pressure, the compound transitioned into a conductor and improved its absorption capabilities for all compounds within the 8–14 eV range, making it suitable for use in the UV spectrum. Cl has the largest absorption among all compounds, whereas I displays the lowest. Reflectivity ranges from around 14% to 18% for all compounds and increases w%ith pressure. The actual component of the refractive index ranges from around 2.25 to 2.7 at 0 eV and increases with pressure. Chlorine has a low refractive index, whereas iodine demonstrates the greatest. The highest fluctuation is shown for Br. The dielectric characteristics vary from around 5 to 7.5 F/m. Chlorine (Cl) has the least charge storage capacity, while iodine (I) demonstrates the most, of which both increase with pressure in all compounds. Structure FrGeX3 (X = Cl, Br, I) is hardened and made more ductile by applying hydrostatic pressure, as seen by the increasing bulk, Young’s, and shear modulus values, as well as the elastic constants (C11 and C12). While the electrons were in a co-linear position, the magnetic property was also studied by optimizing the band structure and density of states. The diamagnetic property of the combination FrGeX3 (where X = Cl, Br, I) remained unchanged even when subjected to increased pressure. According to the findings, this perovskite material has remarkable absorption properties, which point to a change in its behavior from semiconductor to metal. Their potential uses in solar cells, UV absorbers, and optoelectronic devices are highlighted by these computational results.